Hydrometallurgical Processing of Sulfide Minerals from the Perspective of Semiconductor Electrochemistry: A Review - Toledo, Ailton Guilherme Rissoni [UNESP]; Bevilaqua, Denise [UNESP]; Panda, Sandeep; Akcil, Ata (Elsevier, 2023)
The purpose of this article is to explore potential solutions for hydrometallurgical processes using semiconductor electrochemistry as an approach, that has received limited attention from the scientific community. Hydrometallurgy involves more sustainable methods for obtaining metallic resources through dissolution, offering the possibility to leach low-grade ores and recycle waste with low metal concentrations. Several minerals of interest are semiconductors, such as stibnite (Sb2S3), chalcopyrite (CuFeS2), chalcocite (Cu2S), bornite (Cu5FeS4), and sphalerite (ZnS). Thus, understanding the nature of these minerals in contact with an electrolyte solution is crucial for promoting efficiency and scalability of hydrometallurgy, as the efficiency of the reactions involved in the process is dictated by the charge transfer at the interface between the semiconductor and the electrolyte solution containing the redox pairs. Furthermore, this article proposes new models and cost-effective strategies for solubilizing ores from the perspective of semiconductor electrochemistry.
Keywords: Bioleaching; Dissolution; Hydrometallurgy; Ore; Semiconductor electrochemistry